Social support influence on decision-making and its relationship with academic achievement - Eva Noviana Budiyanti (Institute of Education, International Islamic University Malaysia, 2013)
Social support is one of the external factors that can influence students' decision-making abilities and students' achievement. As such, this study attempted to examine the social support influence on students decision-making and to investigate differences in students' achievement among different levels of social support and decision-making. The study was conducted at International Islamic University Malaysia (IIUM) among undergraduate and postgraduate students. The specific aspects of this study were: (1) to investigate any differences in gender, level of study, and nationality on social support received; (2) to investigate any differences in decision-making between gender, nationality and level of study; (3) to investigate the relationship between social support and decision-making among IIUM students; (4) to investigate any significant differences in the level of social support received by students of different achievement levels; and (5) to investigate any significant differences in the level of decision-making of the different achievement levels. The study used a survey research design whereby the data were collected from 377 students by using a stratified random procedure, based on gender, nationality and level of study. Descristive and inferential statistics were employed to analyze the data and to test the hypotheses. Five hypotheses were tested in this study. The results indicated that there were significant differences in social support received among students of different gender, nationality, and level of study. However, the differences in the students' decision-making were not statistically significant. The study also found a statistically significant positive relationship between the social support received and students' decision-making. In addition, differences among categories of students' achievement did not show significant results when tested against types of support received. However, differences among these groups of students were found to be statistically significant when tested against other support aspect in students' decision-making abilities.